Konsep Ketetapan Allah Dalam (Kejadian 21:1-7) - Esra, Cange; Lugu, Suryaman (Institut Agama Kristen Negeri Tarutung, 2023)
Discussion about God's decrees in this increasingly modern era, of course, may not be interesting anymore, because each person must have a different perspective on God's decrees. There are those who accept all the facts that occur as God's decrees, but there are also those who insist that these things happened because of mere human actions. Some say that God's decree is the best for humans, and God's decree was not made at the push of any events or history. This study uses the chiastic structure method with a literary analysis approach, especially in analyzing the structure of the pericope. First of all the author determines the structure of the texts in the passage (Genesis 21:17) begins by analyzing the literal translation in the original language of the text, then conducts word studies in the text being discussed. As a result of this research, the authors found that, God's decree is a decree that is not influenced by anything and anyone and cannot be canceled by anyone for any reason. This article was written to provide insight for readers who are still confused about the concept of God's decree, and this article can also be a reference for writers of scientific papers that discuss the topic of this article. So, God's decree can be said as a journal of life which is then lived by humans.